Optimizing AI as an Instrument for Personal Data Protection within the National Legal Framework - Naavi’u Emal Maaliki (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2025)
Massive data breaches on electronic platforms indicate a legal enforcement gap caused by technological asymmetry. This study aims to analyze the urgency of optimizing Artificial Intelligence (AI) as an instrument for personal data protection within the national legal framework to overcome the limitations of manual supervision. This study employs normative legal research with a statute approach and a comparative approach toward regulations in the United Kingdom and Malaysia. The results indicate that AI can be positioned as a manifestation of the corporate due diligence principle, capable of transforming data protection from a reactive to a proactive-mitigative paradigm through Privacy by Design mechanisms. Furthermore, the legal comparison emphasizes the need for Indonesia's independent supervisory authority to adopt accountable security algorithm standards. The optimization of AI is not merely a technological adoption but a juridical necessity to fill the technical norm vacuum in the PDP Law, ensuring the fundamental right to privacy and information sovereignty of citizens in the era of digital disruption.